Mirror surface aluminum alloy and method for manufacturing the same

CN117718336BActive Publication Date: 2026-10-27CHINALCO MATERIALS APPL RES INST CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311594346.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2026-10-27
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

[0005]本公开的目的在于提供一种镜面铝合金及其制备方法,以解决现有技术中已知镜面铝合金材料的表面粗糙度和Cube织构占比高所导致的表面光泽度不足的技术问题

Benefits of technology

[0016]本申请通过对热轧阶段的乳液参数,热精轧的中间道次变形量、温度-速率,以及冷轧阶段的道次变形量联合调控,并配合阳极氧化阶段的特定化学抛光时间,降低了镜面铝合金的表面粗糙度和Cube织构占比,从而将光泽度显著提高至800GU以上,满足了高品质产品使用要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004572390490000151
    Figure BDA0004572390490000151
  • Figure BDA0004572390490000161
    Figure BDA0004572390490000161
Patent Text Reader

Abstract

The present application relates to a kind of mirror surface aluminum alloy and its preparation method.The preparation method of mirror surface aluminum alloy includes the following steps: making aluminum alloy ingot to carry out homogenization heat treatment, obtain the homogenized aluminum alloy ingot;Make the homogenized aluminum alloy ingot to carry out hot rolling, obtain hot-rolled plate;Make the hot-rolled plate to carry out pre-annealing, obtain pre-annealed plate;Make the pre-annealed plate to carry out cold rolling, obtain cold-rolled plate;Make the cold-rolled plate to carry out mirror surface rolling, obtain mirror surface rolling plate;Make the mirror surface rolling plate to carry out finished annealing, obtain finished plate;Make the finished plate to carry out anodic oxidation, obtain mirror surface aluminum alloy.The present application is through to hot rolling stage's emulsion parameter, hot finishing's intermediate pass deformation, temperature-rate, and the pass deformation of cold rolling stage is jointly controlled, and cooperate with the specific chemical polishing time of anodic oxidation stage, reduce the surface roughness and Cube texture ratio of mirror surface aluminum alloy, to significantly improve glossiness to 800GU above, meet the use requirement of high-quality product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy technology, and in particular to a high-gloss mirror aluminum alloy and its preparation method. Background Technology

[0002] Mirror-finish aluminum products require extremely high surface quality and exhibit high gloss after anodizing. They are primarily used in automotive trim parts, cosmetic casings, and other applications. The gloss of mirror-finish aluminum products is mainly related to two factors: firstly, the surface roughness of the aluminum material. Lower roughness results in less diffuse light reflection, higher reflectivity, and thus greater gloss. Secondly, during the anodizing process, anodized micropores tend to accumulate and grow near the cube texture. If the cube texture is unevenly distributed or constitutes a large proportion, it leads to an increase in surface micropores, increasing light loss and reducing the gloss of the aluminum surface, either locally or overall. Therefore, to improve the gloss of mirror-finish aluminum, it is essential to reduce the surface roughness of the sheet material and decrease the proportion of the cube texture in the aluminum alloy.

[0003] In the production process of mirror aluminum, there are many factors that affect the surface roughness and cube texture distribution: ① Hot rolling emulsion lubrication, insufficient lubrication will lead to aluminum sticking problem, resulting in increased surface roughness; ② Hot rolling is the core process for controlling the cube texture ratio. The hot finishing rolling pass distribution, final rolling temperature and speed all have a significant impact on the cube texture ratio; ③ Cold rolling-annealing process, increasing the total cold rolling deformation can effectively disperse the cube texture distribution and improve the hardness of mirror aluminum products; ④ Mirror rolling process, the roll roughness and pass distribution will significantly affect the surface roughness of mirror aluminum products.

[0004] Patent CN110976515A controls the lubricating oil in the mirror rolling stage by adding 3-12% additives, but does not study the emulsion lubrication in the hot rolling stage. Patent CN113714285A controls the number of passes with a reduction >40% in the hot rough rolling process, but does not specify requirements for the temperature and strain rate in the hot rough rolling stage. Patent CN113106308A controls the cold rolling-annealing process, but does not study the impact of the pre-annealing-cold rolling process on the microstructure. With the development of mirror aluminum products, the requirements for the surface quality of mirror aluminum are becoming increasingly stringent. 750GU can no longer meet the requirements of high-end products, therefore, further optimization of the production process and preparation method is needed. Summary of the Invention

[0005] The purpose of this disclosure is to provide a mirror-finish aluminum alloy and its preparation method, so as to solve the technical problem of insufficient surface gloss caused by the high surface roughness and cube texture ratio of known mirror-finish aluminum alloy materials in the prior art.

[0006] To achieve the above objectives, according to one aspect of this disclosure, a method for preparing mirror-finish aluminum alloy is provided, the method comprising the following steps: step S1, subjecting an aluminum alloy ingot to a homogenization heat treatment to obtain a homogenized aluminum alloy ingot; step S2, hot rolling the homogenized aluminum alloy ingot to obtain a hot-rolled plate, wherein the hot rolling includes hot roughing and hot finishing, and in the hot finishing, the deformation amount in intermediate passes is 20-30%, the exit temperature is 250°C-280°C, and the exit strain rate is 25 s. -1 ~35s -1 The hot rolling process uses an emulsion with a concentration of 7.0 wt% to 8.0 wt%, with an average emulsion particle size of 2 to 4 μm for hot rough rolling and 4 to 6 μm for hot finish rolling. Step S3 involves pre-annealing the hot-rolled plate to obtain a pre-annealed plate. Step 4 involves cold rolling the pre-annealed plate to obtain a cold-rolled plate, wherein the deformation amount in the first pass of cold rolling is 20 to 25%, and the deformation amount in the remaining passes is >30%. Step S5 involves mirror rolling the cold-rolled plate to obtain a mirror-finished plate. Step S6 involves finished annealing the mirror-finished plate to obtain a finished plate. Step S7 involves anodizing the finished plate to obtain a mirror-finished aluminum alloy, wherein the chemical polishing time during anodizing is 60 to 80 seconds.

[0007] Furthermore, in step S1, the homogenization heat treatment temperature is 470℃~490℃, and the time is 10~12h.

[0008] Furthermore, in step S2, the maximum single-pass deformation of the hot roughing is ≤45%, and the strain rate of the hot roughing is greater than 1s. -1 At that time, the temperature of hot rough rolling is 360℃~400℃.

[0009] Furthermore, in step S2, the temperature of the roll is 80°C to 90°C.

[0010] Furthermore, in step S2, in the hot-rolled emulsion particles, particles with a particle size ≥5μm account for ≥30%.

[0011] Furthermore, in step S3, the hot-rolled sheet is pre-annealed after being coiled, and the pre-annealing temperature is 300℃~320℃.

[0012] Furthermore, in step S5, the deformation amount of each pass in mirror rolling is ≤25%, and the number of passes is ≥3.

[0013] Furthermore, in step S2, the emulsion is an O / W type emulsion, comprising base oil, emulsifier, additives and water.

[0014] According to another aspect of this disclosure, a mirror-finished aluminum alloy prepared by the method described in this invention is provided.

[0015] Furthermore, the surface roughness of the mirror-finished aluminum alloy is ≤0.1μm, the proportion of cube texture is ≤6%, and the average grain size is ≤60μm.

[0016] This application reduces the surface roughness and cube texture ratio of mirror-finish aluminum alloys by jointly controlling the emulsion parameters in the hot rolling stage, the deformation amount and temperature-rate of intermediate passes in hot finishing rolling, and the deformation amount of each pass in the cold rolling stage, and by coordinating with the specific chemical polishing time in the anodizing stage, thereby significantly improving the gloss to over 800 GU and meeting the requirements for high-quality products. Detailed Implementation

[0017] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present disclosure will now be described in detail with reference to the embodiments.

[0018] To address the shortcomings of the prior art mentioned in the background section, a specific embodiment of this disclosure provides a method for preparing mirror-finish aluminum alloys. The method includes the following steps: Step S1, subjecting an aluminum alloy ingot to a homogenization heat treatment to obtain a homogenized aluminum alloy ingot; Step S2, hot-rolling the homogenized aluminum alloy ingot to obtain a hot-rolled plate, wherein the hot rolling includes hot roughing and hot finishing rolling. In the hot finishing rolling, the deformation amount in intermediate passes is 20-30%, the exit temperature is 250℃-280℃, and the exit strain rate is 25s. -1 ~35s -1 The hot rolling process uses an emulsion with a concentration of 7.0 wt% to 8.0 wt%, with an average emulsion particle size of 2 to 4 μm for hot rough rolling and 4 to 6 μm for hot finish rolling. Step S3 involves pre-annealing the hot-rolled plate to obtain a pre-annealed plate. Step 4 involves cold rolling the pre-annealed plate to obtain a cold-rolled plate, wherein the deformation amount in the first pass of cold rolling is 20 to 25%, and the deformation amount in the remaining passes is >30%. Step S5 involves mirror rolling the cold-rolled plate to obtain a mirror-finished plate. Step S6 involves finished annealing the mirror-finished plate to obtain a finished plate. Step S7 involves anodizing the finished plate to obtain a mirror-finished aluminum alloy, wherein the chemical polishing time during anodizing is 60 to 80 seconds.

[0019] This application reduces the surface roughness and cube texture ratio of mirror-finish aluminum alloys by jointly controlling the emulsion parameters in the hot rolling stage, the deformation amount and temperature-rate of intermediate passes in hot finishing rolling, and the deformation amount of each pass in the cold rolling stage, and by coordinating with the specific chemical polishing time in the anodizing stage, thereby significantly improving the gloss to over 800 GU and meeting the requirements for high-quality products.

[0020] Hot rolling plays a decisive role in reducing cube texture. Controlling the deformation amount in intermediate hot finishing passes, lowering the hot finishing rolling temperature, and increasing the hot finishing rolling rate can all effectively reduce the proportion of cube texture. By controlling the hot rolling process, the cube texture in hot-rolled plates can be reduced to below 6%.

[0021] For example, in the hot finishing rolling of step S2, the deformation amount of intermediate passes can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%. For example, in the hot finishing rolling of step S2, the exit strain rate can be 25 s⁻¹. -1 26s -1 27s -1 28s -1 29s -1 30s -1 31s -1 31s -1 33s -1 34s -1 or 35s -1 .

[0022] Mirror-finish aluminum alloys have a high Mg content and low hardness, making them prone to aluminum adhesion during high-temperature hot rolling. Once aluminum powder is pressed into the surface of the aluminum plate, it will create pits, affecting surface roughness and reducing gloss. Therefore, the concentration of the emulsion used in hot rolling needs to be controlled between 7.0 wt% and 8.0 wt% to increase lubrication. In this paper, the emulsion includes base oil, emulsifier, additives, and water. Emulsion concentration refers to the volume percentage of all substances in the emulsion except water, based on the total volume of the emulsion.

[0023] For example, in step S2, hot rolling can use emulsions with concentrations of 7.0 wt%, 7.1 wt%, 7.2 wt%, 7.3 wt%, 7.4 wt%, 7.5 wt%, 7.6 wt%, 7.7 wt%, 7.8 wt%, 7.9 wt%, or 8.0 wt%.

[0024] The ease of water-oil separation is related to the emulsion particle size and hot rolling temperature. Hot finishing rolling results in significantly higher stability than hot roughing rolling, making water-oil separation more difficult; therefore, emulsions with larger particle sizes are required. An average particle size of 2–4 μm for hot roughing and 4–6 μm for hot finishing emulsions prevents excessively small particle sizes, which would lead to overly stable emulsions and hinder water-oil separation during use, thus reducing lubrication and causing aluminum adhesion. In this paper, the average emulsion particle size refers to the average particle size of the dispersed phase (oil) in the water.

[0025] For example, in step S2, the average particle size of the hot-rolled emulsion can be 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3.0μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, or 4μm.

[0026] For example, in step S2, the average particle size of the hot-rolled emulsion can be 4μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, or 6μm.

[0027] The main purpose of controlling the deformation amount in the first pass of cold rolling to 20-25% is to prevent excessive deformation, thereby preventing incomplete removal of alumina or aluminum powder from the pre-annealed sheet surface from being pressed into the sheet, causing irreversible indentations that can be passed on to the finished product. The first pass of cold rolling utilizes the coolant to remove contaminants such as alumina or aluminum powder from the sheet surface. If the deformation amount is too small, slippage can easily occur, reducing production efficiency; therefore, controlling the deformation amount in the first pass to 20-25% is appropriate. For example, in the cold rolling step S4, the deformation amount in the first pass can be controlled to 20%, 21%, 22%, 23%, 24%, or 25%.

[0028] In aluminum alloys, different elements exhibit varying reflectivities for light wavelengths of different lengths. Among them, only Cu (Cu) shows an increase in reflectivity with increasing wavelength, which effectively compensates for the slow decrease in reflectivity of Al alloys with increasing wavelength, especially for light wavelengths above 500 nm. However, adding Cu to aluminum alloys can exacerbate corrosion. During the chemical polishing stage of anodizing, the corrosion reaction intensifies with increasing Cu content, significantly reducing surface roughness. Therefore, the chemical polishing time needs to be controlled within 60–80 seconds to prevent excessively long reaction times, which would increase surface roughness and consequently affect the gloss after anodizing.

[0029] For example, during the anodizing process in step S7, the chemical polishing time can be 60s, 61s, 62s, 63s, 64s, 65s, 66s, 67s, 68s, 69s, 70s, 71s, 72s, 73s, 74s, 75s, 76s, 77s, 78s, 79s, or 80s.

[0030] In some instances, in step S1, the homogenization heat treatment temperature is 470℃~490℃, and the time is 10~12h. Homogenization heat treatment is well known to those skilled in the art, and they can select the temperature and time of homogenization heat treatment according to actual needs.

[0031] For example, in step S1, the homogenization heat treatment temperature can be 470℃, 471℃, 472℃, 473℃, 474℃, 475℃, 476℃, 477℃, 478℃, 479℃, 480℃, 481℃, 482℃, 483℃, 484℃, 485℃, 486℃, 487℃, 488℃, 489℃, or 490℃, and the time can be 10h, 11h, or 12h.

[0032] In some instances, in step S2, the maximum single-pass deformation of the hot rolling is ≤45%, and the strain rate of the hot rolling is greater than 1 s. -1 The hot rolling temperature is 360℃~400℃. By performing hot rolling under these conditions, the surface roughness and cube texture ratio of mirror-finish aluminum alloys can be further reduced, thereby improving surface gloss.

[0033] For example, in step S2, the maximum single-pass deformation of the hot roughing can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, or 45%.

[0034] In some instances, the roll temperature is 80°C to 90°C in step S2. Maintaining the roll temperature within the range of 80°C to 90°C further ensures the stability of the emulsion's performance during hot rolling.

[0035] For example, in step S2, the temperature of the roll can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, or 90°C.

[0036] In some instances, in step S2, the proportion of emulsion particles with a diameter ≥5μm in the hot-rolled emulsion is ≥30%, preferably ≥40%. This is mainly to prevent the water-oil separation effect of the emulsion from decreasing when the hot rolling temperature is low. Increasing the proportion of large-diameter particles in the emulsion can effectively reduce the stability of the emulsion and has a significant improvement effect on the hot-rolling stage.

[0037] In some instances, in step S3, the hot-rolled sheet is pre-annealed after being coiled, with the pre-annealing temperature being 300℃~320℃. Pre-annealing is well known to those skilled in the art, and they can select the pre-annealing temperature and time according to actual needs.

[0038] For example, in step S3, the pre-annealing temperature can be 300℃, 301℃, 302℃, 303℃, 304℃, 305℃, 306℃, 307℃, 308℃, 309℃, 310℃, 311℃, 312℃, 313℃, 314℃, 315℃, 316℃, 317℃, 318℃, 319℃, or 320℃.

[0039] In some instances, in step S5, the deformation amount per pass of mirror rolling is ≤25%, and the number of passes is ≥3. The more passes of mirror rolling, the better it is for reducing surface roughness; multiple passes with small deformations make it easier to obtain a finer surface.

[0040] For example, in step S5, the deformation amount of each pass in mirror rolling can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%.

[0041] In some instances, in step S2, the emulsion is an O / W type emulsion comprising a base oil, emulsifier, additives, and water. Those skilled in the art can select the desired emulsion based on actual needs.

[0042] According to another embodiment of this article, a mirror-finished aluminum alloy prepared by the above-described method of the present invention is provided.

[0043] This application reduces the surface roughness and cube texture ratio of mirror-finish aluminum alloys by jointly controlling the emulsion parameters in the hot rolling stage, the deformation amount and temperature-rate of intermediate passes in hot finishing rolling, and the deformation amount of each pass in the cold rolling stage, and by coordinating with the specific chemical polishing time in the anodizing stage, thereby significantly improving the gloss to over 800 GU and meeting the requirements for high-quality products.

[0044] In some examples, the surface roughness of the mirror-finish aluminum alloy is ≤0.1μm, the cube texture ratio is ≤6%, and the average grain size is ≤60μm.

[0045] In some instances, the surface gloss of mirror-finished aluminum alloys is ≥800 GU, the color difference value is ≤0.25, and the material texture occurrence rate is ≤2%.

[0046] In this application, the composition and content of aluminum alloy ingots and mirror-finished aluminum alloys are not limited. Those skilled in the art can select appropriate compositions and contents as needed. For example, in aluminum alloy ingots and mirror-finished aluminum alloys, by weight, Si ≤ 0.1%, Fe ≤ 0.1%, Cu: 0.1–0.3%, Mg: 0.8–2.2%, Mn ≤ 0.8%, the total of other impurity elements ≤ 0.1%, and the remainder is Al. Further, in aluminum alloy ingots and mirror-finished aluminum alloys, by weight, 0.01% ≤ Si ≤ 0.1%, 0.01% ≤ Fe ≤ 0.1%, Cu: 0.1–0.3%, Mg: 0.8–2.2%, 0.1% ≤ Mn ≤ 0.8%, the total of other impurity elements ≤ 0.1%, and the remainder is Al.

[0047] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0048] Example

[0049] In the following examples and comparative examples, the percentages of each component used refer to the weight percentage of the corresponding component.

[0050] Example 1

[0051] The composition of the aluminum alloy ingot (by weight) is as follows: Si 0.08%, Fe 0.05%, Cu 0.2%, Mg 2.0%, Mn 0.5%, other impurity elements totaling 0.1%, and the remainder being Al.

[0052] The preparation process of mirror-finish aluminum alloy:

[0053] Step S1: The aluminum alloy ingot is subjected to homogenization heat treatment at 480°C for 12 hours to obtain a homogenized aluminum alloy ingot.

[0054] Step S2 involves hot rolling the homogenized aluminum alloy ingot to obtain a hot-rolled plate, wherein the hot roughing rolling strain rate is greater than 1 s. -1 At that time, the rolling temperature was controlled at 360-370℃, the maximum single-pass deformation of hot roughing was 45%; the deformation of intermediate passes in hot finishing was 25%, the exit temperature of hot finishing was 280℃, and the exit strain rate of hot finishing was 30s. -1 The concentration of the emulsion sprayed during the hot rolling process is 8.0% (hot roughing emulsion preparation: Hofton's Tandemol 6600 series products + water; hot finishing emulsion preparation: Hofton's Tandemol 6200 series products + water). The average particle size of the emulsion in hot roughing is 4μm, the average particle size of the emulsion in hot finishing is 5μm, the proportion of particles with a particle size ≥5μm is 50%, and the roll temperature is 80℃.

[0055] Step S3: The hot-rolled plate is pre-annealed at 320°C for 2 hours to obtain a pre-annealed plate;

[0056] Step S4: The pre-annealed plate is cold-rolled to obtain a cold-rolled plate. The deformation amount of the first pass of cold rolling is 20%, and the deformation amount of the remaining passes is >30%.

[0057] Step S5: Perform mirror rolling on the cold-rolled sheet to obtain a mirror-rolled sheet. The deformation amount of each mirror rolling pass is ≤25%, and the number of passes is 3.

[0058] Step S6: Anneal the mirror-finished rolled sheet at 330°C for 2 hours to obtain the finished sheet;

[0059] Step S7 involves anodizing the finished plate to obtain a mirror-finish aluminum alloy. The anodizing process is as follows, and the plate is thoroughly rinsed with pure water after each step:

[0060] ①Alkaline washing: Wash with 90g / L NaOH solution at 75℃ for 20s;

[0061] ② Neutralization: Wash with 200g / L HNO3 solution at 25℃ for 20s;

[0062] ③ Chemical polishing: Clean with an aqueous solution of H3PO4:H2SO4 in a volume ratio of 4:1 at 90°C for 80 seconds;

[0063] ④ Anodizing: Use 180 g / L H2SO4 solution and apply an electric current for 15 min at 20℃;

[0064] ⑤ Sealing: Use pure water to keep warm at 90℃ for 30 minutes.

[0065] Example 2

[0066] Composition of aluminum alloy ingot (by weight): Si 0.08%, Fe 0.05%, Cu 0.3%, Mg 1.8%, Mn 0.3%, other impurity elements totaling 0.1%, the remainder being Al;

[0067] The preparation process of mirror-finish aluminum alloy:

[0068] Step S1: The aluminum alloy ingot is subjected to homogenization heat treatment at 480°C for 12 hours to obtain a homogenized aluminum alloy ingot.

[0069] Step S2 involves hot rolling the homogenized aluminum alloy ingot to obtain a hot-rolled plate, wherein the hot roughing rolling strain rate is greater than 1 s. -1At that time, the rolling temperature was controlled at 390-400℃, the maximum single-pass deformation of hot roughing was 45%; the deformation of intermediate passes in hot finishing was 30%, the exit temperature of hot finishing was 250℃, and the exit strain rate of hot finishing was 25s. -1 The concentration of the emulsion sprayed during the hot rolling process was 7.0% (the only difference from the emulsion in Example 1 was the concentration). The average particle size of the emulsion in the hot rough rolling was 2 μm, the average particle size of the emulsion in the hot finish rolling was 6 μm, the proportion of particles with a particle size ≥ 5 μm was 63%, and the roll temperature was 80°C.

[0070] Step S3: Pre-anneal the hot-rolled plate at 300°C for 2 hours to obtain a pre-annealed plate;

[0071] Step S4: The pre-annealed plate is cold-rolled to obtain a cold-rolled plate. The deformation amount of the first pass of cold rolling is 25%, and the deformation amount of the remaining passes is >30%.

[0072] Step S5: Perform mirror rolling on the cold-rolled sheet to obtain a mirror-rolled sheet. The deformation amount of each mirror rolling pass is ≤20%, and the number of passes is 4.

[0073] Step S6: Anneal the mirror-finished rolled sheet at 330°C for 2 hours to obtain the finished sheet;

[0074] Step S7, except for ③, is the same as in Example 1:

[0075] ③ Chemical polishing: A solution with a volume ratio of H3PO4:H2SO4 of 4:1 was used for cleaning at 90℃ for 60 seconds.

[0076] Example 3

[0077] Except for step S2, where the average particle size of the emulsion in hot rough rolling is 3 μm, the average particle size of the emulsion in hot finish rolling is 4 μm, and the proportion of particles with a particle size ≥ 5 μm is 42%, all other steps are the same as in Example 1.

[0078] Example 4

[0079] Except for step S2, where the intermediate pass deformation is 20% and the exit strain rate is 35s. -1 Except for the steps, all other steps are the same as in Example 1.

[0080] Example 5

[0081] Except for the emulsion concentration of 7.5% in step S2, all other steps are the same as in Example 1.

[0082] Example 6

[0083] Except for step S4, where the deformation amount of the first pass is 23% and the deformation amount of the remaining passes is >30%, all other steps are the same as in Example 1.

[0084] Example 7

[0085] Except for the chemical polishing time of 70s in step S7, all other steps are the same as in Example 1.

[0086] Comparative Example 1

[0087] Composition of aluminum alloy ingot (by weight): Si 0.08%, Fe 0.05%, Cu 0.2%, Mg 2.0%, Mn 0.5%, other impurity elements totaling 0.1%, the remainder being Al;

[0088] The preparation process of mirror-finish aluminum alloy:

[0089] Step S1: The aluminum alloy ingot is subjected to homogenization heat treatment at 480°C for 12 hours to obtain a homogenized aluminum alloy ingot.

[0090] Step S2 involves hot rolling the homogenized aluminum alloy ingot to obtain a hot-rolled plate, wherein the hot roughing rolling strain rate is greater than 1 s. -1 At that time, the rolling temperature was controlled at 360℃; the deformation amount of the intermediate passes in the hot finishing rolling was 35%, the exit temperature of the hot finishing rolling was 290℃, and the exit strain rate of the hot finishing rolling was 20s. -1 The emulsion concentration was 9.0% (the only difference from the emulsion in Example 1 was the concentration), the average particle size of the hot rough-rolled emulsion was 4 μm, the average particle size of the hot finish-rolled emulsion was 5 μm, the proportion of particles with a particle size ≥ 5 μm was 50%, and the roll temperature was 80°C.

[0091] Step S3: The hot-rolled plate is pre-annealed at 320°C for 2 hours to obtain a pre-annealed plate;

[0092] Step S4: The pre-annealed plate is cold rolled to obtain a cold-rolled plate. The deformation amount of the first pass of cold rolling is 18%, and the deformation amount of the remaining passes is >30%.

[0093] Step S5: Perform mirror rolling on the cold-rolled sheet to obtain a mirror-rolled sheet. The deformation amount of each mirror rolling pass is ≤25%, and the number of passes is 3.

[0094] Step S6: Anneal the mirror-finished rolled sheet at 330°C for 2 hours to obtain the finished sheet;

[0095] Step S7 involves anodizing the finished plate to obtain a mirror-finish aluminum alloy. The anodizing process is as follows, and the plate is thoroughly rinsed with pure water after each step:

[0096] ①Alkaline washing: Wash with 90g / L NaOH solution at 75℃ for 20s;

[0097] ② Neutralization: Wash with 200g / L HNO3 solution at 25℃ for 20s;

[0098] ③ Chemical polishing: Clean with a solution of H3PO4:H2SO4 in a volume ratio of 4:1 at 90°C for 50 seconds;

[0099] ④ Anodizing: Use 180 g / L H2SO4 solution and apply an electric current for 15 min at 20℃;

[0100] ⑤ Sealing: Use pure water to keep warm at 90℃ for 30 minutes.

[0101] Comparative Example 2

[0102] Except for step S2, where the exit temperature of hot finishing is 330°C, the average particle size of the emulsion in hot finishing is 3μm, and the proportion of particles with a particle size ≥5μm is 20%, all other steps are the same as in Example 1.

[0103] Comparative Example 3

[0104] Except for step S2, where the exit temperature of the hot finishing mill is 250℃ and the exit strain rate is 15s. -1 Except for the average particle size of the emulsion from hot rough rolling being 2 μm and the chemical polishing time in step S7 being 120 s, all other steps are the same as in Example 1.

[0105] Performance testing

[0106] 1. Average grain size

[0107] The average grain size was determined according to GB / T 6394-2017 (Method for Determination of Average Grain Size of Metals).

[0108] 2. Cube texture proportion

[0109] EBSD testing and analysis were performed using a scanning electron microscope (model: JSM-7800F). Five samples were selected within a 100×100mm area for testing, and the average value was taken.

[0110] 3. Surface roughness

[0111] Surface roughness was tested according to GB / T 1031-1995.

[0112] 4. Gloss

[0113] According to GB / T 12967.6-2022 (Test Methods for Anodized Films and Organic Polymer Films of Aluminum and Aluminum Alloys), a gloss meter (model: 3nh-HG268) was used for testing.

[0114] 5. Color difference value

[0115] According to GB / T 12967.6-2022 (Test methods for aluminum and aluminum alloy anodized films and organic polymer films - Part 6: Color difference and appearance quality), a colorimeter (model: 3nh-NR110) was used for testing.

[0116] 6. Material texture generation rate

[0117] The surface texture of 100×100mm samples was statistically analyzed using a visual method.

[0118] Table 1 shows the performance test results of Examples 1-7 and Comparative Examples 1-3:

[0119] Table 1

[0120]

[0121]

[0122] The results above show that the mirror aluminum alloy prepared by the method of the present invention has a surface roughness of ≤0.1μm, a cube texture ratio of ≤6% and a discrete distribution, and an average grain size of ≤60μm; after anodizing, the surface gloss is ≥800GU, the color difference value is ≤0.25, and the material texture generation rate is ≤2%.

[0123] Compared with Comparative Examples 1-3, the method of the present invention can achieve the following technical effects:

[0124] This application reduces the surface roughness and cube texture ratio of mirror-finish aluminum alloys by jointly controlling the emulsion parameters in the hot rolling stage, the deformation amount and temperature-rate of intermediate passes in hot finishing rolling, and the deformation amount of each pass in the cold rolling stage, and by coordinating with the specific chemical polishing time in the anodizing stage, thereby significantly improving the gloss to over 800 GU and meeting the requirements for high-quality products.

[0125] The above embodiments are merely descriptions of the technical solutions of this disclosure and are not intended to limit its scope. Although those skilled in the art can make various modifications based on the above examples, all modifications should be within the protection scope of this disclosure as long as they do not depart from its design spirit.

[0126] The above description only relates to specific embodiments of this disclosure and is not intended to limit this disclosure. Various modifications and variations can be made to this disclosure by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this disclosure should be included within the scope of protection of this disclosure.

Claims

1. A method for preparing mirror-finish aluminum alloy, characterized in that, Includes the following steps: Step S1 involves subjecting the aluminum alloy ingot to a homogenization heat treatment to obtain a homogenized aluminum alloy ingot. Step S2 involves hot rolling the homogenized aluminum alloy ingot to obtain a hot-rolled plate. The hot rolling includes hot roughing and hot finishing. In the hot finishing, the deformation in intermediate passes is 20-30%, the exit temperature is 250-280°C, and the exit strain rate is 25 s. -1 ~35s -1 Furthermore, the hot rolling process uses an emulsion with a concentration of 7.0% to 8.0%, the average particle size of the emulsion in the hot rough rolling process is 2 to 4 μm, and the average particle size of the emulsion in the hot finish rolling process is 4 to 6 μm; in the emulsion particles of the hot finish rolling process, particles with a particle size ≥ 5 μm account for ≥ 30%; Step S3: Pre-anneal the hot-rolled plate to obtain a pre-annealed plate; Step S4: The pre-annealed plate is cold-rolled to obtain a cold-rolled plate, wherein in the cold rolling, the deformation amount in the first pass is 20-25%, and the deformation amount in the remaining passes is >30%. Step S5: Perform mirror rolling on the cold-rolled sheet to obtain a mirror-rolled sheet; Step S6: Perform finished product annealing on the mirror-finished rolled plate to obtain the finished plate; Step S7 involves anodizing the finished plate to obtain a mirror-finished aluminum alloy, wherein the chemical polishing time during the anodizing process is 60-80 seconds.

2. The method according to claim 1, characterized in that, In step S1, the homogenization heat treatment is performed at a temperature of 470℃~490℃ for 10~12 hours.

3. The method according to claim 1 or 2, characterized in that, In step S2, the maximum single-pass deformation of the hot roughing is ≤45%, and the strain rate of the hot roughing is greater than 1s. -1 At that time, the temperature of the hot roughing was 360℃~400℃.

4. The method according to claim 1 or 2, characterized in that, In step S2, the temperature of the roll is 80℃~90℃.

5. The method according to claim 1 or 2, characterized in that, In step S3, the hot-rolled plate is pre-annealed after being coiled, and the pre-annealing temperature is 300℃~320℃.

6. The method according to claim 1 or 2, characterized in that, In step S5, the deformation amount of each pass in the mirror rolling is ≤25%, and the number of passes is ≥3.

7. The method according to claim 1 or 2, characterized in that, In step S2, the emulsion is an O / W type emulsion, comprising base oil, emulsifier, additives and water.

8. A mirror-finish aluminum alloy prepared by any one of claims 1-7.

9. The mirror-finish aluminum alloy according to claim 8, characterized in that, The surface roughness of the mirror aluminum alloy is ≤0.1μm, the proportion of cube texture is ≤6%, and the average grain size is ≤60μm.

Citation Information

Patent Citations

  • Mirror rolling method for high-gloss 8000 series mirror aluminum alloy plate and strip

    CN110976515A

  • Fine-grain homogeneous mirror surface aluminum alloy rolled plate strip and preparation method thereof

    CN113106308A

  • Anodic oxidation rolled mirror surface aluminum plate strip and preparation method thereof

    CN113714285A

  • Hot-rolled plate for mirror surface aluminum, preparation method of hot-rolled plate and preparation method of part containing hot-rolled plate

    CN115109970A

  • Hot rolling oil composition for aluminum and emulsion type hot rolling oil for aluminum

    JP1999343494A